Economic and social outcomes of investment on infrastructure and early warning system in Tajikistan’s agrifood system - Khakimov, Parviz; Aragie, Emerta A.; Goibov, Manuchehr; Ashurov, Timur (International Food Policy Research Institute, 2025)
Irrigation and timely access to sufficient volumes of water are vital to increase crops productivity, rural incomes, and food security (FAO 2023; World Bank 2021). In Tajikistan, irrigation sector faces several challenges and constraints such as: aged, poorly maintained infrastructure and poor management system that led low-quality irrigation services; limited investment in drainage infrastructure, inadequate maintenance, poor water management, and harmful irrigation practices that led salinization and waterlogging in some irrigated areas. In addition, the ongoing process of climate change and rising temperatures will increase crop water demands, while water supply reliability will decline, leading to more-severe, more-frequent water stress. The minimum required operation and maintenance on irrigation infrastructure estimated to be about US$35 million per year. Around 85 percent of cultivated land is irrigated and provides more than 90 percent of the total value of crop production. Since independence, the condition and performance of irrigation infrastructure has declined because of severe underfinancing.